Cerebrovascular Diseases and Risk Factors: a Strategy of Primary Prevention - Miguel Angel Buergo Zuaznábar; Rubén Bembibre Taboada (Medisur)
Cerebrovascular diseases constitute a health problem worldwide and have the tendency to grow up. Chronic diseases sometimes are considered transmissible diseases at a level of risk factors. The alimentary habits and the levels of physical activity at present are risk behaviors which are spread all over the world passing from one population to another as an infectious disease with incidence in the morbidity profiles worldwide. While age and sex as well as genetic vulnerability are no modifiable elements, great part of the risks associated to age and sex can be reduced. In such risks, behavior factors (alimentary habits, physical inactivity, smoking habit and alcoholism), biological factors (dyslipidemia, hypertension, overweight, and hyperinsulinemia) and finally the social factors which cover a complex combination of socio-economic, cultural parameters, and other elements of the environment that interact among them. This work covers risk factors and the behavior to be followed for its modification.